1997
DOI: 10.1123/jtpe.16.2.196
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the Qualitative Measures of Teaching Performance Scale as a Measure of Teacher Effectiveness

Abstract: The purpose of this study was to determine the relationship between the Qualitative Measures of Teaching Performance Scale (QMTPS; Rink & Werner, 1989) and teacher effectiveness in producing student achievement. The QMTPS focuses primarily on variables related to teacher clarity and task presentation. Nine middle school generalist (classroom) teachers were asked to teach the volleyball forearm pass and serve over eight lessons as part of their normal curriculum. Students were pre- and posttested on the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
11

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
2
16
0
11
Order By: Relevance
“…The purpose of the present study was to determine the relationship between students' achievement in qualitative and quantitative performance of manipulative skills and ALT-PE categories. Results indicated that students improved and retained their performance in throwing and catching after the eight-lesson unit, a finding that is consistent with previous studies (i.e., Gusthart, Kelly & Rink, 1997), even though the teaching goal was sport skills learning.…”
Section: Discussionsupporting
confidence: 89%
“…The purpose of the present study was to determine the relationship between students' achievement in qualitative and quantitative performance of manipulative skills and ALT-PE categories. Results indicated that students improved and retained their performance in throwing and catching after the eight-lesson unit, a finding that is consistent with previous studies (i.e., Gusthart, Kelly & Rink, 1997), even though the teaching goal was sport skills learning.…”
Section: Discussionsupporting
confidence: 89%
“…They consistently demonstrated each task, used qualitative cues, and provided congruent feedback to learners. The work of Gusthart, Kelly, & Rink (1997) supports the use oftotal QMTPS score over several lessons as a measure of achievement.…”
Section: Rues: September 2001mentioning
confidence: 76%
“…The South Carolina Experience is used as a clear example of success in how policy and accountability can work together to create positive changes in PE at the state level. Historically, Rink has set the pace in identifying and assessing effective teaching in PE (Gusthart, Kelly, & Rink, 1997;Rink 2010;Rink & Mitchell, 2003). However, Rink's (2013) ideas deviate from those of McKenzie and Lounsbery when it comes to narrowing the curriculum.…”
Section: Effective Teaching and The Role Of Accountability: A Bumpy Rmentioning
confidence: 91%